108k views
4 votes
I need 4 more tryna go to sleep rn :/

I need 4 more tryna go to sleep rn :/-example-1
User Antken
by
4.9k points

1 Answer

2 votes

Answer:

Hello!!! Princess Sakura here ^^

Explanation:

It is
y=2x+2 because you should use
m=(y_(2)-y_(1) )/(x_(2)-x_(1) ) then just plug it in using

(1, 4) and (-2, -2).


(4--2)/(1--2) =(6)/(3) =2

That eliminates everything except the second one and the third.

So now we would find the b in the equation
y=mx+b


y=mx+b\\4=2(1)+b\\4=2+b\\2=b\\b=2

and that's all

User Troy Hunt
by
5.5k points